Chemical structure-related mechanisms underlying in vivo genotoxicity induced by nitrofurantoin and its constituent moieties in gpt delta rats. (4th May 2015) - Kijima, Aki; Ishii, Yuji; Takasu, Shinji; Matsushita, Kohei; Kuroda, Ken; Hibi, Daisuke; Suzuki, Yuta; Nohmi, Takehiko; Umemura, Takashi
Abstract: Nitrofurans are antimicrobial compounds containing a nitro group at the 5-position of the furan ring and an amine or hydrazide side chain derivative. One member of the nitrofurans, nitrofurantoin (NFT), is a renal carcinogen in male rats despite its still controversial genotoxicity. We investigated chemical structure-related modes of action of NFT, and reporter gene mutation assays for NFT and its constituent moieties were performed. NFT, 5-nitro-2-furaldehyde (NFA), or 1-aminohydantoin (AHD) was administered to male F344 gpt delta rats by gavage for 4 or 13 weeks at a carcinogenic or the maximum tolerated dose. NFT caused a significant increase in gpt mutant frequency (MF) at 13 weeks with G-base substitution mutations. An increase in gpt MF was also observed in the NFA-treated group at 13 weeks, but not in the AHD-treated group. 8-Hydroxydeoxyguanosine (8-OHdG) levels in the kidney DNA of NFT-treated rats were significantly increased after 4 weeks. NFT caused accumulation of hyaline droplets indicated by positive immunostaining and western blot analysis for α2u -globulin in the proximal tubules. An additional study, in which female gpt delta rats were given NFT at the same dose used for males, was performed to mitigate the effect of α2u -globulin. NFT exerted the same effects on female rat kidneys to the same extent as males in terms of gpt MF and 8-OHdG level. Thus, it is highly probable that the structure of the nitro furan plays a key role in NFT-induced genotoxicity and genotoxic mechanisms including oxidative DNA damage are involved in NFT-induced renal carcinogenesis. α2u -globulin-mediated nephropathy may be a prerequisite for NFT-induced renal carcinogenesis in male rats, and additionally NFT could be a latent carcinogen in female rats and other animal species.